A transdisciplinary approach to adolescent safeguarding education. (2nd October 2021) - Littler, Nadine
Abstract : Background: Adolescent safeguarding is a key public health issue, which requires a transdisciplinary approach to address the range of safeguarding risks seen within this critical period of development. Aims: The aim of this research study was to explore the need for adolescent safeguarding education within transdisciplinary programmes. Methods: A qualitative descriptive study was undertaken with participants studying or teaching on nursing, policing, social work, youth work and teaching programmes at a North-West University in England. Participation involved either the completion of a JISC online questionnaire or an informal interview, the data of which was analysed using thematic analysis. Findings: Two key themes were identified in the data; safeguarding education and professional culture, and three subthemes: curriculum content and delivery and professional identity. Conclusions: This study has highlighted the need to adopt a life-course (adolescence) and hybrid approach (uniprofessional and transdisciplinary) to safeguarding education in transdisciplinary programmes.